Artificial Intelligence Technology and The Challenge of Sustainable National Development in Nigeria - Poronakie, Nwiekpugi Bright (PhD); Ihejirika, Happiness (PhD) (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This paper examines the obvious critical national development problems in Nigeria and strategies to be adopted to ensure livelihood sustainability in her space-economy, including its citizens that have complex, diverse cultural backgrounds. The major problems are high insecurity rate, mass poverty, unemployment, corruption and poor access to basic infrastructural facilities due to inefficient exploitation and utilization of the natural resources leading to environmental devastation and economic underdevelopment of the minority ethnic groups in the country. The problems are also traced to lack of transparency and accountability in governance, dominated by three major ethnic groups in the country leading to political instability and increasing state of insecurity occasioned by militant organizations across Nigeria. Hence, the need arises to design and adopt modern security strategies like the artificial intelligence technology that is applied in advanced countries during covid-19 pandemic than mere lockdown in Nigeria. This technology is used to combat insecurity and save people’s lives headlong to enhance socio-economic stability and sustainable national development in the country. Therefore, the paper recommends the electronic voting system, organization of national conference, adequate provision of basic amenities, cultural reform, review of all existing laws regulating oil and gas development, immediate fixing of the refineries and other income-generating facilities, economic diversification, build and strengthen institutional structures and improve capacity-building strategy using modern artificial intelligence technologies for adequate security network services in Nigeria